What Do Mothers Learn from Children's Science Television?. Issue 2 (15th March 2021) - Watts, Judy; Bonus, James Alex
ABSTRACT: Mothers and their 4- to 5-year-old children ( N = 46) watched one of two versions of an educational science television show. One version modeled didactic instruction (i.e., imparting factual knowledge), whereas the other version modeled inquiry instruction (i.e., encouraging investigation). Children struggled to learn from either video. However, the video that modeled didactic instruction taught mothers new factual information, and the video that modeled inquiry instruction increased mothers' instructional self-efficacy. Despite these improvements, neither video changed the way that mothers discussed science with their children during a related activity. Recommendations for future research and for content creators are provided.